2020
DOI: 10.1093/nar/gkaa222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2′-5′/3′-5′ phosphodiester linkage heterogeneity on RNA interference

Abstract: We report on the synthesis of siRNAs containing both 2′-5′- and 3′-5′-internucleotide linkages and their effects on siRNA structure, function, and interaction with RNAi proteins. Screening of these siRNAs against their corresponding mRNA targets showed that 2′-5′ linkages were well tolerated in the sense strand, but only at a few positions in the antisense strand. Extensive modification of the antisense strand minimally affected 5′-phosphorylation of the siRNA by kinases, however, it negatively affected siRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…For strand-nicking cleavage assays utilizing radiolabeled target DNA strands, individual DNA strands (cpEGIPe target sequence) were 5′ radiolabeled with T4 polynucleotide kinase and 32 P-γ-ATP as previously described 112 . Radiolabeled DNA strands were then gel-purified from a 15% denaturing Urea-PAGE by crushand-soak elution after visualizing radioactive bands by autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…For strand-nicking cleavage assays utilizing radiolabeled target DNA strands, individual DNA strands (cpEGIPe target sequence) were 5′ radiolabeled with T4 polynucleotide kinase and 32 P-γ-ATP as previously described 112 . Radiolabeled DNA strands were then gel-purified from a 15% denaturing Urea-PAGE by crushand-soak elution after visualizing radioactive bands by autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…4 ) is well tolerated in the sense strand. 77 Some 2′–5′ phosphate linkages are tolerated on antisense strand, but modification of all six nucleotides from AS:1 to AS:6 reduced activity nearly 8-fold. Positional screening revealed that none of the first six linkages played a substantially larger role than the others and that up to two modifications are relatively well tolerated.…”
Section: Internal Modificationsmentioning
confidence: 99%
“…Except in exceptional circumstances, increasing the number of 2 ,5 -phosphodiester bonds reduces siRNA activity, which may be attributed to less siRNA binding to the AGO2 protein. Another study discovered that siRNAs containing a mixture of 2 ,5 /3 ,5 -phosphodiester bonds on the AS were more effective at silencing genes than siRNAs containing only 2 ,5 -phosphodiester bond modifications [93].…”
Section: Phosphate Backbone Modificationmentioning
confidence: 99%